Designing of a specific fluorogenic peptide substrate for HIV-1 protease activity assay - Hong Loan, Nguyen Thi; Thu Huyen, Tran Thi; Lieu, Dang Thi; Lam Hong, Phan Thi; Nghia, Phan Tuan (Academia Journal of Biology, 2016)
Based on the specific hydrolysis sequence in the Gag-Pol protein substrate of HIV-1 protease, we designed a fluorescence resonance energy transfer (FRET) substrate (designated peptide HF) for the enzyme. peptide HF has the sequence of QXL 520-GABA-SFNFPQITK-HiLyte Flour 488-NH2. HiLyte Fluor 488/QXL 520 as a FRET pair because of high excitation/emission and good activity at the optimal pH of HIV-1 protease (pH<5) was chosen. QXL 520 was more stable when conjugated with serine residue at N-terminus via GABA group while leucine at the C-terminus was replaced with a lysine residue-HiLyte Fluor 488 conjugate. The optimal reaction conditions for HIV-1 protease activity assay were found to include 100-200 ng HIV-1 protease, 2 µM peptide HF, 100 mM CH3COONa buffer at pH 4.7, containing 1 M NaCl, 1 mM EDTA, 1 mM DTT, 5% DMSO and 0.5 mg/mL BSA. Peptide HF could be stored at the concentration of 0.1 mg/mL in DMSO and at -80oC until use. Under the above mentioned conditions, HIV-1 protease showed the high affinity and the effective hydrolysis for the substrate with the kinetic parameters Vmax of 4.45 nM/s, Kcat/Km = 10.89 (mM.s)-1, which were 5 times higher than the Vmax and Kcat/Km when the commercial SensoLyte® 520 substrate (Anaspec-America) was used.   Citation: Nguyen Thị Hong Loan, Tran Thi Thu Huyen, Dang Thi Lieu, Phan Thi Lam Hong, Phan Tuan Nghia, 2017. Designing of a specific fluorogenic peptide substrate for HIV-1 protease activity assay. Tap chi Sinh hoc, 39(1): 115-121.  DOI: 10.15625/0866-7160/v39n1.8291. *Corresponding author: loannhbio@gmail.com Received 1 May 2016, accepted 20 December 2016